2004
DOI: 10.1562/2004-03-03-ra-097.1
|View full text |Cite
|
Sign up to set email alerts
|

Rose Bengal–Sensitized Photooxidation of the Dipeptides l-Tryptophyl-l-Phenylalanine, l-Tryptophyl-l-Tyrosine and l-Tryptophyl-l-Tryptophan: Kinetics, Mechanism and Photoproducts¶

Abstract: The Rose Bengal-sensitized photooxidations of the dipeptides l-tryptophyl-l-phenylalanine (Trp-Phe), l-tryptophyl-l-tyrosine (Trp-Tyr) and l-tryptophyl-l-tryptophan (Trp-Trp) have been studied in pH 7 water solution using static photolysis and time-resolved methods. Kinetic results indicate that the tryptophan (Trp) moiety interacts with singlet molecular oxygen (O(2)((1)Delta(g))) both through chemical reaction and through physical quenching, and that the photooxidations can be compared with those of equimole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…This is not a common behavior using a dipeptide or other polypeptide, whose peptide bond influences considerably the reactivity. 42 However, it has been shown that the reaction with peptides containing tryptophan mainly forms compounds 1 and 3, and in smaller amounts kuinurenine derivative 5. 43 Reaction in aqueous solutions between tryptophan and 1 O 2 was carried out using different photosensitizers, 44,45 and the reaction products were identified by chromatographic techniques and spectrometric methods.…”
Section: Tryptophanmentioning
confidence: 99%
“…This is not a common behavior using a dipeptide or other polypeptide, whose peptide bond influences considerably the reactivity. 42 However, it has been shown that the reaction with peptides containing tryptophan mainly forms compounds 1 and 3, and in smaller amounts kuinurenine derivative 5. 43 Reaction in aqueous solutions between tryptophan and 1 O 2 was carried out using different photosensitizers, 44,45 and the reaction products were identified by chromatographic techniques and spectrometric methods.…”
Section: Tryptophanmentioning
confidence: 99%
“…However, LC-MS 2 analysis found that all of the mass altered peptides were derived solely from oxidative modification of Trp. When the reactions of Trp containing dipeptides with 1 O 2 were studied, structures corresponding to mass increments of +4, +16 and +32 were identified as suggested in Figure 1B [11] [49]. Consistent with our observation of +48 and -59 photochemical products, additional peaks attributed to addition of two O 2 molecules and subsequent fragmentations were observed when Trp-Phe was reacted with 1 O 2 [49] however mass spectrometry does not provide sufficient information to unequivocally assign structures to these modifications.…”
Section: Modification Of Peptides By 1 Omentioning
confidence: 99%
“…Both transformations are reversible. Tyr and Trp in peptide sequences should be protected from sunlight, as both amino acids are at risk of photo-oxidation [ 7 ]. The rate of racemization in solid-phase peptide synthesis is common and depends on many factors, including the electron-withdrawing effect of the amino acid side chain, the temperature, the reaction solvent, and the coupling reagents [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%